Enhancements and User-Centered Innovations in AI in Libraries - Suryakanth Halburga (Scientific Research, New Technologies and Applications Vol. 2, 2024)
Library services are transforming because of artificial intelligence (AI), which is bringing about major improvements and user-focused innovations that improve accessibility, effectiveness, and user engagement. This article examines how artificial intelligence (AI) transforms libraries, emphasizing important technologies including computer vision, natural language processing, and machine learning. The organization and finding of materials are streamlined by AI-driven automated cataloging and metadata management, and improved search capabilities yield more relevant and accurate results. Artificial Intelligence (AI) supports digital preservation initiatives by guaranteeing the longevity and availability of vital materials. Chatbots and virtual assistants provide 24/7 assistance, enhancing customer happiness and lightening the workload of employees. The user experience is enhanced by automated resource management and personalized recommendations, making library visits more productive and enjoyable. Furthermore, AI powers immersive technologies like virtual and augmented reality and improves accessibility for those with impairments. It also makes interactive learning easier through educational platforms. Libraries may ethically utilize AI’s promise by tackling obstacles and moral issues like prejudice and data privacy. This article highlights AI’s critical role in contemporary libraries by showing how these advancements provide more welcoming, inclusive spaces that change to meet the communities’ changing requirements.